PROBLEMATIKA KELUARGA DENGAN POLA KARIR GANDA (Studi Kasus di Wilayah Mangir, Sendangsari, Pajangan, Bantul, Yogyakarta) - Nur Endah Januarti * (Pendidikan Sosiologi FIS UNY, 2010)
Problematic families with dual career path describes the life patterns of families with dual careers or families with a composition of husband and wife who are both working. Case studies conducted in the Territory Mangir, Sendangsari, Displays, Bantul, Yogyakarta. This study aims to: 1) Knowing the family background with dual career path to choose multiple career patterns in family life; 2) Knowing the various problems faced; 3) Knowing how to overcome various problems encountered. The following research using qualitative methods. Research resource persons were family members along with a third party if the family has a maid or relatives who live together. Research subjects taken by purposive sampling. The process of data collection is done by semi-structured interviews, non-participatory observation, field recording, and documentation. Researchers used the instrument in the form of interview guidelines and guidelines for observation. Checking the validity of data using triangulation techniques. Techniques in data analysis is data reduction, data presentation, and conclusion. The results showed that: 1) family background choose multiple career patterns in the family was at first a husband and wife are both working and the next because there is a principle or desire to get couples to work; 2) The problems that occur a variety of them ( a) not to participate in social activities, (b) the limited ability of parents to accompany the development of children's learning process, (c) unanticipated expenditures related to contributions to a celebration activities in the community and colleagues in the office, (d) no homework completion ladder well, (e) the rules of time to work all the time / not stabilized, (f) communication eg for